THE IMPACT OF ECO-FRIENDLY AND NUTRIENT RICH ORGANIC FOOD PRODUCTS ON CONSUMER`S PURCHASE INTENTIONS IN MALAYSIAN POPULATION - Johar,; MGM,; Yajid, Mohd Shukri Ab; Shukri, Shakeerah Mohd (International Journal of Psychosocial Rehabilitation, 2020)
Organic foods are becoming popular in today’s modern world. People’s awareness towards the importance of healthy foods consumption has increased. The critical importance in stabilizing the style of living by consuming healthy protein by safe additives, safe flavorings, save colorings, save preservatives and those that are claimed to be pesticides-free has been the main focus for many consumers nowadays. The focus of this study and to examine the extent to which the Malaysian consumers would accept the type of food offered in the markets and examine factors like food safety, food quality and eco-friendly nature of organic food that influence the consumers’ acceptance toward organic foods in Malaysia. The conclusion of this study will assist the organic foods suppliers to strategize and improve the selection of food adaptable in markets of Malaysia that will help the sustainability of the company in the long run.